2001
DOI: 10.1152/jappl.2001.91.6.2686
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the fatigability of arm muscles depends on absolute force during isometric contractions

Abstract: Women are capable of longer endurance times compared with men for contractions performed at low to moderate intensities. The purpose of the study was 1) to determine the relation between the absolute target force and endurance time for a submaximal isometric contraction and 2) to compare the pressor response and muscle activation patterns of men [26.3 +/- 1.1 (SE) yr] and women (27.5 +/- 2.3 yr) during a fatiguing contraction performed with the elbow flexor muscles. Maximal voluntary contraction (MVC) force wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
284
6
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 294 publications
(349 citation statements)
references
References 46 publications
49
284
6
9
Order By: Relevance
“…The greater fatigability when high CD was imposed during the isometric sustained contractions in young adults was associated with baseline strength [16] such that weaker individuals were more susceptible to increased fatigability, possibly as a result of altered muscle perfusion [11,12,16]. This was achieved because we were able to match some of the male and female cohort for strength [16].…”
Section: Discussionmentioning
confidence: 99%
“…The greater fatigability when high CD was imposed during the isometric sustained contractions in young adults was associated with baseline strength [16] such that weaker individuals were more susceptible to increased fatigability, possibly as a result of altered muscle perfusion [11,12,16]. This was achieved because we were able to match some of the male and female cohort for strength [16].…”
Section: Discussionmentioning
confidence: 99%
“…TIME TO TASK FAILURE of a sustained submaximal isometric contraction (i.e., endurance time, ET) depends on physiological factors such as relative force level (30,35), muscle fiber type composition (16,51,77), muscular activation strategy (6,19,38), muscle size (36), and length (54,58) but also depends on psychological factors such as motivation, mood, and expectation (24). Whereas the task dependency of ET is well documented (23,25,26), little is known about muscle fatigue characteristics induced by a given task sustained until failure in different muscle groups, in the same individuals.…”
mentioning
confidence: 99%
“…The gender difference in muscle endurance is believed to be related to factors such as muscle mass, energy metabolism, and muscular tissue (Hicks et al 2001). Hunter and Enoka (2001) suggested that because people with larger muscle strength must maintain larger, absolute muscle strength when using the fixed, relative demand value, they are judged to be inferior in muscle endurance. Even when performing work with the same relative intensity, males exert larger muscle forces than females.…”
Section: Discussionmentioning
confidence: 99%